A Museum Proposal for Today’s Society: the “Liquid Museum” - Vieira Gonçalves, Juan Carlos (Eikón / Imago, 2019)
This article aims to explore the idea of the “liquid museum” argued by Van Oost and Cameron: a museological paradigm that seeks to adapt to current society, this society being observed as a “liquid society” that lives in a “liquid modernity”. Delegating the task of elaborating bases for a more critical and constructive vision of the concept and contemporary museological practice, what is intended here is a reflection in which the museum is presented as a fluid, polysemic and adaptable institution. The aim is to reconcile the notion of the “liquid museum” with an effective and functional museological practice shared and participated in which the principles of co-responsibility, cooperation and inclusion of society in the work of museums are essential factors for the increase of a true liquid work.